Evaluation of Influencing Factors and Technological Processes for the Production of Orange Essential Oil (Citrus sinensis) on Equipment Semi-industrial Distillation - Huynh Bao Long; Tran Thien Hien; Hoang Quang Binh; Xuan Tien Le (Universitas Gadjah Mada, 2022)
In recent years, essential oils extracted from different plant species have become increasingly popular in the production of pharmaceuticals, cosmetics, and foods. The essential oil from orange (Citrus sinensis) is important in large-scale applications due to its antibacterial, antioxidant activities, and pleasant aroma. In this study, factors affecting the production of orange essential oil on a distillation device with an operating capacity of 50 L/batch, including the ratio of material to water, temperature, and time distillation, have been surveyed. Through the survey, it was found that the raw materials were pureed, the materials: water ratio was 1:3 g/g, the water heating temperature was 130 °C, and the distillation time was 140 min. The yield of the essential oil was 1.8 mL/g with compounds limonene accounting for 98%, α-Pinene (0.655–0.734%), and β-Pinene (1.114 and 1.163%) by the GC-MS method. The review also found that the hydrodistillation equipment was designed to be suitable for the semi-industrial scales of orange essential oil due to its stable yield and volatile compounds contained in the essential oil.